Self-focusing of a spatially modulated beam within the paraxial complex geometrical optics framework in low-density plasmas. (9th November 2021) - Ruocco, A; Duchateau, G; Tikhonchuk, V T
Abstract: Accurate modelling of ponderomotive laser self-focusing may represent a key for the success of inertial confinement fusion, especially within the shock ignition approach. From a numerical point of view, implementation of a paraxial complex geometrical optics (PCGO) method has improved the performance of the hydrodynamics code CHIC, but (1) overestimating ponderomotive speckle self-focusing in reduced two-dimensional geometry, and (2) not accounting for speckle intensity statistics. The first issue was addressed in our previous work (Ruocco et al 2019 Plasma Phys. Control. Fusion 61 115009). Based on those results, here we propose a novel PCGO scheme for modelling spatially modulated laser beams by (1) creating Gaussian speckles, and (2) emulating the realistic speckle intensity statistics. Self-focusing of spatially modulated beams in a homogeneous stationary plasma with this method is studied. This investigation evidences that plasma smoothing does not reduce the speckle intensity enhancement at long time scales when the average beam intensity is twice above the speckle critical intensity. Comparison against electromagnetic simulations confirms that this approach improves the description of self-focusing of high-intensity speckles within the PCGO model.